Nigella sativa L. as immunomodulator and preventive effect on renal tissue damage of lupus mice induced by pristane - Zahrah Hikmah; Anang Endaryanto; I. Dewa Gede Ugrasena; Anny Setijo Rahaju; Syaiful Arifin (Heliyon, 2022)
Introduction: Nigella sativa L. is an herbal plant with Thimoquinone as the main therapeutic properties. This plants has been shown to cure for various diseases and affected the immune system by modulating cytokines and T regulatory cell (Treg) sot that able to prevent renal injury in several diseases, but studies on Systemic Lupus Erythematous are still rare. Objective: This study aimed to investigate immunomodulation and preventive effects of Nigella sativa L. on renal tissue damage in Pristane induced Lupus (PIL)-mice model. Methods: This true experimental study included 48 female Balb/C mice, 38 mice were injected pristane intraperitoneally and waited 16 weeks to become lupus model. Only 30 mice met the Systemic Lupus International Collaborating Clinics criteria. Ten healthy mice were used as control, 30 PIL mice model divided into 3 groups (placebo, steroid, Nigella sativa L.). At the end of 28 days of treatment, the mice were sacrificed to take a blood sample and kidney organ to evaluate the injury histopathologically. Results: The results showed that the cytokine expression Interleukin (IL) (IL-17, IL-6, IL-23) in the Nigella sativa L. group was the lowest. The highest absolute number of Tregs was the steroid group followed Nigella sativa L. group. Renal injury assessed histopathologically showed the Nigella sativa L. group was the lowest and almost close to normal. Conclusion: This study indicate that Nigella sativa L. has an immunomodulatory effect and can prevent kidney injury PIL-treated mice. We suggest that Nigella sativa L. may need to be considered for further research on its use as a complementary supplement in lupus patients.